Application of comparative sonochemical, photochemical, and sono-photochemical methods to obtain new silicon phthalocyanine with high singlet oxygen efficiency - Atmaca, Goknur Yasa; Celep, Kevser; Erdogmus, Ali (ELSEVIER SCIENCE SA, 2024)
Nowadays, non-invasive and nontoxic therapy methods are preferred to treat diverse types of cancer. Sonophotodynamic therapy (SPDT) is one of these alternative methods, combining the properties of PDT (photodynamic therapy) and SDT (sonodynamic therapy) and resulting in a higher singlet oxygen generation. The efficiency of this method is increased by synthesizing a complex with enhanced photochemical properties to use as a sensitizer. Phthalocyanines, especially with added derivatives holding diamagnetic metals such as Si4+, are often compounds used in PDT studies owing to their efficient yields of singlet oxygen formation. In this study, 4-hydroxy-7-methoxyquinoline silicon phthalocyanine was synthesized and its anti-cancer therapy effect rates were calculated and compared by photochemical and sono-photochemical methods in DMSO. This research will help the studies that aim to obtain high singlet oxygen efficiency in therapeutic methods.
Keywords: Silicon phthalocyanine; Synthesis; Photosensitizer; Sono-photodynamic therapy; SONODYNAMIC THERAPY; IN-VITRO; PHOTODYNAMIC THERAPY; BREAST-CANCER; SUBSTITUENTS; DERIVATIVES; EFFICACY; Chemistry